Suriname. Significant achievements 2016 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The main activities carried out by the Institute in Suriname during 2016 are identified, with respect to the needs and interests of the country, strengthening issues such as risk management, governance, agribusiness, sustainability, renewable energy, composting, organic agriculture, food security and nutritional, safety and agricultural health. Likewise, work was done on managing drought, the use of biofuels, technology, economic rehabilitation and the control of pests and diseases, such as the carambola fruit fly. Finally, support was given to rehabilitating the soil and improving the production of aquatic animals.